This is exactly the same problem as was asked and answered last weekend, elsewhere...
Prove this formula for the Fibonacci Sequence - Mathematics - Stack Exchange
The fibonacci sequence, F(n) is defined:
F(n) = F(n-1) + F(n-2) for each n = 2,3,... with F(0)=1 and F(1)=1.
Use strong induction to prove that
F(n) = [PHI^(n+1)-(-PHI)^(-n-1)] / (sqrt(5)) for each integer n greater than or equal to 0.
Where PHI=(1+sqrt(5))/2
Please help!!
This is exactly the same problem as was asked and answered last weekend, elsewhere...
Prove this formula for the Fibonacci Sequence - Mathematics - Stack Exchange